Authorship Trends in Ghana Journal of Agricultural Science: A Bibliometric Study - Kwadzo, G.; Annor, G. (Ghana Library Journal, 2007)
The paper examined authorship patterns of feature articles, research and development notes, subject review articles, provisional communications and documentation in the Ghana Journal of Agricultural Science (GJAS). Content analysis was undertaken to collect feature articles, research and development notes, subject review articles, provisional communications and documentation in the GJAS from 36 volumes, published over a 35 year period (1968-2003). Authors\’ institutional and geographic affiliations were examined. Descriptive statistics was used in analyzing the data. A total of 663 articles authored by 1202 authors were analysed. Results indicated that 332 articles were single-authored while 331 were co-authored. The proportion of single-authored papers had decreased from 90% in 1968 to 6.25% in 2003. During the period, there was an increase in average number of authors per paper from 1.10 in 1968 to 2.87 in 2003. Degree of collaboration also increased from 0.10 to 0.94. The research should sensitize Ghanaian authors to collaborate more with experts from outside Ghana, especially from the developed world.